A three-dimensional printed biomimetic hierarchical graphene architecture for high-efficiency solar steam-generation. Issue 37 (11th September 2020) - Wang, Zhuoyue; Liu, Hanwen; Chen, Fengjuan; Zhang, Qiangqiang
Abstract : A three-dimensional biomimetic hierarchical graphene architecture for high-efficiency solar steam-generation which is constructed by direct writing-based 3D printing. Abstract : In solar-assisted steam generators, simultaneously realizing high sunlight absorption and water transportation is a significant challenge. In this study, inspired by natural transpiration and the hierarchical architecture of artificial origami, we developed a three-dimensional (3D) graphene oxide-based solar steam generator (GOSG), which was delicately designed and constructed via direct writing-based 3D printing coupled with freeze-drying. The obtained GOSG features a rippled upper surface decorated with stomata-like pores, while its substructures comprise hierarchical biomimetic structures with vertically orientated vessel-like channels serving as the basic capillary tubes for water transportation. Benefiting from the elaborate multi-scale structure design and the chemical modification of oxygenic functional groups, the as-printed 3D GOSG realizes the synergistic integration of improved performances, including wide spectra sunlight absorption, rapid water transportation, heat localization, and vapor evaporation. In the systematic investigation of the solar-thermal conversion processes, the GOSG device showed a superior efficiency of up to 94.5% under illumination as high as 1 kW m −2, which is greater than those of most reported systems. The water desalination and sewage treatment abilities of the GOSG were further validated, demonstrating its multifunctional applications. Moreover, the prototype device tested for solar-assisted steam generation at an outdoor site demonstrated excellent mechanical robustness, cycling durability, and diverse applicability, indicating the great potential of the GOSG as a high-efficiency, customizable, and scalable solar steam generator. These outstanding properties of the GOSG confirm that the combination of composition modification and structure optimization in a multi-scale design is an effective strategy for significantly improving the solar steam generation performance.